Penerapan Pendekatan Teaching at The Right Level (TaRL) dengan Model Problem Based Learning (PBL) Guna Meningkatkan Hasil Belajar Matematika Siswa SMA - Nila Azizatil Ludfiana; Sugiyanti Sugiyanti; Ganang Iqbal Riska; Nurina Happy (Departement of Mathematics Education, 2024)
This research is motivated by the low mathematics learning outcomes, which is a crucial issue in the development of education, particularly at SMA Negeri 9 Semarang. This study is an Action Research (PTK). The aim of this research is to determine whether Teaching at the Right Level (TaRL) with Problem-Based Learning (PBL) can improve students' mathematics learning outcomes. The subjects involved in this study were 36 students from class XII SMA N 9 Semarang. The research was conducted in two cycles. The results of the research show that teaching using the Teaching at the Right Level (TaRL) approach with Problem-Based Learning (PBL), starting from cycle 1 to cycle 2, resulted in an improvement in students' mathematics learning outcomes. In Cycle I, the percentage of learning outcomes reached 66.67%, which increased to 88.89% in Cycle II. The implementation of the Teaching at the Right Level (TaRL) approach with Problem-Based Learning (PBL) has proven to enhance the mathematics learning outcomes of students in class XII SMA N 9 Semarang.